Fault Detection in Wireless Sensor Network Based on Deep Learning Algorithms - Regin, R.; Rajest, S. Suman; Singh, Bhopendra (EAI Endorsed Transactions on Scalable Information Systems, 2021)
This paper is about Fault detection over a wireless sensor network in a fully distributed manner. First, we proposed the Convex hull algorithm to calculate a set of extreme points with the neighbouring nodes and the duration of the message remains restricted as the number of nodes increases. Second, we proposed a Naïve Bayes classifier and convolution neural network (CNN) to improve the convergence performance and find the node faults. Finally, we analyze convex hull, Naïve bayes and CNN algorithms using real-world datasets to identify and organize the faults. Simulation and experimental outcomes retain feasibility and efficiency and show that the CNN algorithm has better-identified faults than the convex hull algorithm based on performance metrics.
Keywords: Wireless sensor network; Fault detection; Convolution neural network; convex hull; Naive-Bayes; performance metrics and energy efficiency